PENGARUH FAKTOR PEMBELAJARAN TERHADAP PERKEMBANGAN MORAL DAN KEPRIBADIAN SISWA SEKOLAH DASAR: STUDI SURVEI KORELASIONAL DI SDN 15 SIKAKAP - Safitri, Sanseni; Silviana Evi Vitriani Taileleu; Yeni Karneli; Zelhendri Zen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Moral and personality development constitutes a fundamental dimension of basic education that shapes students' long-term social character and civic behavior. This study aimed to examine the influence of four key learning factors, namely teacher role modeling, positive classroom climate, successful learning experiences, and peer acceptance, on the moral and personality development of elementary school students aged 6–12 years at SDN 15 Sikakap, Kepulauan Mentawai Regency. A quantitative correlational survey design was employed with a sample of 77 students from grades 1–6, selected through total sampling. Data were collected using structured Likert-scale questionnaires measuring moral development based on Kohlberg's theory and personality development based on Erikson's psychosocial theory. Validity was assessed using Pearson product-moment correlation (r>0.30) and reliability via Cronbach's Alpha (α=0.84 for moral scale; α=0.81 for personality scale). Results indicated that students' moral development was categorized as high (M=3.58; SD=0.70), and personality development was similarly high (M=3.31; SD=0.69). The four learning factors collectively explained 58.7% of the variance in students' moral and personality development (R²=0.587; F(4,72)=25.61; p<0.001). Teacher role modeling was the strongest predictor (β=0.38; p<0.001), followed by positive classroom climate (β=0.29; p=0.001), successful learning experiences (β=0.24; p=0.013), and peer acceptance (β=0.19; p=0.030). These findings underscore the pivotal role of a conducive school environment in fostering moral and personality formation of elementary school students. Keywords: moral development, personality development, learning factors, character education, elementary school